A systematic review of school-based physical activity interventions on children's wellbeing. Issue 1 (1st January 2016) - Rafferty, Ruth; Breslin, Gavin; Brennan, Deirdre; Hassan, David
ABSTRACT: Purpose : The aim of this study was to review the effect of school-based physical activity interventions on children's wellbeing. Method : A systematic search of school-based physical activity studies was conducted using EBSCOhost PsycInfo, EBSCOhost Medline and Web of Science. Initially 995 studies were retrieved and, following the removal of duplicates, the titles and abstracts of 984 studies were screened. This screening identified 53 relevant studies from which 42 were excluded, resulting in 11 articles being reviewed. Results : Three studies reported a positive increase in wellbeing; however, only one of those studies also significantly increased physical activity. It was apparent that the measurement of wellbeing and physical activity was inconsistent across studies, making conclusions difficult to draw. The wellbeing measures used neglected to account for the children's perspectives of wellbeing. Conclusions : The effect of a physical activity intervention on increasing wellbeing appears to be more complex than originally believed. The complexity may in part be due to methodological issues and the choice of wellbeing and physical activity measurement. We recommend that future physical activity interventions include a measure of wellbeing developed from the child's perspective, and that future reviews narrow the search to only interventions that have had success at increasing physical activity before exploring effects on wellbeing.